Pendampingan Bagi Kelompok Guru Dalam Membuat Media Pembelajaran Articulate Storyline-3 - Desy Safitri; Sujarwo; Nurzengky Ibrahim; Iqbal Pratama (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This initiative was prompted by the low level of teachers’ proficiency in utilizing digital technology to develop innovative interactive learning materials. Articulate Storyline 3 is an e-learning development software that enables the creation of multimedia-based learning content; however, its use among teachers remains very limited due to a lack of adequate training and guidance. The objective of this activity is to provide guidance to groups of teachers in designing and developing interactive learning media using Articulate Storyline 3, so that teachers are able to create learning experiences that are more engaging, effective, and aligned with students’ needs in the digital age. The mentoring activity was carried out through a series of stages, including orientation, hands-on training, and guidance during the learning media creation process. The methods used included varied lectures, question-and-answer sessions, interactive discussions, demonstrations, simulations, and questionnaire completion. The results of the activity showed an increase in teachers’ knowledge, understanding, and skills regarding the use of Articulate Storyline 3, as reflected in the group’s ability to produce Articulate Storyline 3 educational media products, such as dynamic presentation slides, score-based quizzes, and branching learning scenarios. This activity is expected to encourage the transformation of teachers’ teaching practices toward more innovative learning. This initiative is expected to encourage teachers to transform their teaching practices toward more innovative learning methods, as well as serve as a mentoring model that can be replicated within the broader teaching community.